2006
DOI: 10.1007/s10038-005-0339-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the 3′-untranslated region of the thymidylate synthase gene and sensitivity of stomach cancer to fluoropyrimidine-based chemotherapy

Abstract: Polymorphism in the 3¢-untranslated region of the thymidylate synthase gene and sensitivity of stomach cancer to fluoropyrimidine-based chemotherapy Abstract To investigate the relationship between polymorphism in the 3¢-untranslated region (3¢-UTR) of the thymidylate synthase (TS) gene and sensitivity of gastric cancer to 5-fluorouracil (5-FU)-based chemotherapy, 106 cases of advanced gastric cancer were analyzed. All patients were treated with 5-FU-based chemotherapy; DNA from peripheral blood leukocytes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Discussion miRNAs are known to inhibit gene expression by binding to the 3Ј UTR of the target transcript. 3Ј UTR polymorphisms are reported to be associated with various diseases that include hereditary thrombophilia (32), ␣-thalassemia (33), insulin sensitivity (34), urolithiasis (35), human papilloma virus infection (36,15), and increased sensitivity to 5-fluorouracil chemotherapy (37,38). Recently, it has been shown that a G-to-A transition in the 3Ј UTR of the myostatin gene in Texel sheep creates a potential illegitimate miRNA target site, which recruits miR1 and miR206 binding and leads to translational inhibition of the gene, resulting in muscular hypertrophy (39).…”
Section: Cells Expressing Snp-829c3 T Adjacent To the Mir-24 Binding mentioning
confidence: 99%
“…Discussion miRNAs are known to inhibit gene expression by binding to the 3Ј UTR of the target transcript. 3Ј UTR polymorphisms are reported to be associated with various diseases that include hereditary thrombophilia (32), ␣-thalassemia (33), insulin sensitivity (34), urolithiasis (35), human papilloma virus infection (36,15), and increased sensitivity to 5-fluorouracil chemotherapy (37,38). Recently, it has been shown that a G-to-A transition in the 3Ј UTR of the myostatin gene in Texel sheep creates a potential illegitimate miRNA target site, which recruits miR1 and miR206 binding and leads to translational inhibition of the gene, resulting in muscular hypertrophy (39).…”
Section: Cells Expressing Snp-829c3 T Adjacent To the Mir-24 Binding mentioning
confidence: 99%
“…40 Also SNPs in 3'-UTR are associated with human papilloma virus infection, 41 with increased sensitivity to 5-fluorouracil (5FU) chemotherapy 42,43 and with urolithiasis. 44,45 It has been predicted that a target gene can be regulated by more than one microRNA.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…5,10-Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in folate metabolism, which catalyzes the irreversible conversion of 5-10-methylene tetrahydrofolate to 5-methyltetrahydrofolate (5). Because decreased activity of MTHFR may result in accumulation of 5-10-methylene tetrahydrofolate and improve the antitumor efficacy of FU, several studies evaluated genetic polymorphisms of MTHFR, with or without genetic polymorphisms of TYMS in patients with advanced gastric cancer, although the clinical data are still controversial (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%